Aplikasi War Game Pada Mobile Device Menggunakan Sensor Gyroscope dan Accelerometer - Djuvan Pranoto; Andreas Handojo; Gregorius Satia Budhi (Universitas Kristen Petra, 2022)
Currently technology has developed very rapidly. Along with the development of today's technology, a lot of games - games that have sprung up. The fact is that the game has become a daily activity in society. In today's technological developments, almost everyone has a mobile phone. Where this phone is easy to get and is very flexible. By combining current conditions, this research takes advantage of current technological advances and utilizes the flexibility of mobile phones to be implemented into an application that will become a means of shooting games. This application uses gyroscope and accelerometer sensors to complete this research. The goal is to create new interactions and experiences in mobile games and to create flexible shooting games using today's technology. The result of this research is the success of creating a war game. Which is where this application requires a strong signal and stable internet speed and must be played in an open place. On the other hand, this application has succeeded in providing accurate bullet trajectory distance calculations and bullet estimates with an average difference of ±1-3 meters.